The Moving Strokes - Mohamad Faizuan, bin Mat (2019)
The Moving Strokes is an annual art show organized by Sarawak Artist Society which 2019 will be conducted at Saradise Gallery. The participating artists include Sylvester Wielding Jussem, Awangko' Hamdan from UNIMAS.